Cameroon Public Expenditure Review : Aligning Public Expenditures with the Goals of Vision 2035 - World Bank (World Bank, Washington, DC, 2018)
The analysis presented in this Public Expenditure Review (PER) is designed to support the efforts of the Government of Cameroon (GOC) to enhance public expenditure efficiency and improve the quality of public goods and services. The report reviews public expenditure data over a 10-year period, examines trends in the composition and efficiency of spending, and assesses whether spending patterns are consistent with Cameroon’s development objectives. The report includes an in-depth analysis of public investment, the budget category that has experienced the largest increase over past decade. It also evaluates the fiscal status of state-owned enterprises and explores the evolution of the wage bill, subjects that are especially relevant in Cameroon. Finally, the report reviews public health and education expenditures, which together account for 20.5 percent of total central government spending and which play a pivotal role in socioeconomic development and poverty reduction. The PER’s recommendations are tailored to reflect the government’s current fiscal consolidation effort and the ongoing implementation of its national development strategy. In 2009, the Government adopted the Growth and Employment Strategy Paper (Document de Stratégie pour la Croissance et l’Emploi, DSCE) as part of its overarching development agenda, Vision 2035, which calls for increased spending, a strong role for government in promoting private-sector development, and measures to enhance the delivery of social services. However, since 2014 Cameroon has joined other Central African Economic Community (CEMAC) member states in pursuing fiscal consolidation and expenditure rationalization. The PER offers specific recommendations for increasing expenditure efficiency across multiple sectors of the public administration.